THE EFFECTS OF INTELLECTUAL INTELEGENCE LEVEL AND STUDENTS’ MOTIVATION TOWARDS STUDENTS’ ENGLISH LEARNING ACHIEVEMENT - Dudi Abdul Hamid; Supadi Supadi (Universitas Indraprasta PGRI, 2018)
The Purpouse of this reseach is to know about : the effect of intellectual intelegence level and student’s motivation towards student’s English learning achievement as itself or together. The mode that used in this research is descriptive model. The data that used trhough technic test and cuatitative analysis, show that 1). There are a significant effects of Intellectual Intelegence Level and Student’s Motivation towards Student’s English Learning Achievement as itself or together. The Mode that used in this research is Descriptive Model. The Data that used through technic test and cuantitative analysis, show that There are any significant effects of intellectual intelegence level and student’s motivation together towards student’s English learning achievement at Vocational High School in Sukabumi District of West Java Province. It is approved by the score of Sig. 0,000 < 0,05 and Fh = 20.833. 2). There is a significant effect of intellectual intelegece level towards student’s English learning achievement at Vocational High School in Sukabumi District of West Java Province . it is approved by the score of Sig. 0,000 < 0,05 and th = 3.782. 3). There is a significant effect of student’s motivation toward student’s English learning achievement at Vocational High School in Sukabumi District of West Java Province . it is approved by the score of Sig. 0,000 < 0,05 and th = 4.116. its mean there is a significant effect of student’s motivations and student’s English learning achievement. Key Words : Intellectual Intelegence Level, Students’ Motivation, and Students’ English Learning Achievement